Nonequidistant two-dimensional antenna arrays are based on Latin squares for registration of cosmic, atmospheric and lithospheric radiation - Anh, Nguyen Xuan; Lutsenko, V. I.; Yiyang, Luo; Popov, I. V. (Vietnam Journal of Marine Science and Technology, 2017)
The possibility of using Latin squares for constructing two-dimensional non-equidistant antenna arrays that can be used for development of radio telescopes and systems for remote sensing of atmospheric and lithospheric radiation has been shown. An algorithm for calculating the coordinates of elements of a non-equidistant antenna array using the values of elements of Latin squares is proposed. It is shown that in this case, it is possible to obtain an almost complete coverage of the grid of spatial frequencies in the region of the arrangement of the elements at small filling coefficients of array. Directional patterns are studied and the side lobes levels are estimated for non-equidistant antennas obtained on the basis of Latin squares. The possibility of synthesizing of large antenna arrays on the basis of composite squares using the embedding of generative Latin squares is shown. The characteristics of the obtained arrays are studied. It is shown that using the shifts and mutual rotations of individual layers is involved in the synthesized array; its characteristics can be substantially improved.